J. J. Thomsonovo raziskovanje "negativnih in pozitivnih žarkov" - Južnič, Stanislav (Vakuumist, 2001)
The article reviews the life and research of J. J. Thomson, famous leader of Cavendish laboratory. His key contribution in "discovery" of electron is described. His relations with contemporaries that made him the discoverer of "electron" for the generations to come are described. We also analyze Thomson's research of "positive rays". The echo of his successes among Slovenecon temporaries is mentioned.
Keywords: Thomson, Joseph John, 1856-1940; elektroni; pozitivni žarki; katodni žarki; negativni žarki; biografije; fiziki